SOCIAL INTERACTION BETWEEN MUSLIMS AND CHRISTIANS IN KARANGTURI VILLAGE, SURAKARTA, INDONESIA - Rina Febriyanti; Nurhadi (Jurnal Sosiologi Dialektika Sosial, 2025)
Religious differences in a multicultural society can pose challenges in maintaining social relations. Although this diversity has the potential for conflict, the Karangturi community has succeeded in building a harmonious and peaceful social life. This study aims to examine the forms of social interaction between Muslims and Christians and the strategies of the people of Karangturi Village, Laweyan, Surakarta in maintaining harmony. This study uses a qualitative method with a case study approach. Primary data sources were obtained through in-depth interviews with informants, while secondary data came from various relevant literature and were used as comparison material with previous research. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions to obtain valid research results. The results of the study indicate that interactions are realized through cooperation in social and religious activities, adjustments to the time and place of worship to avoid friction, and the integration of social values ​​through local traditions. Javanese cultural values ​​such as tepa selira (tolerance) and mutual cooperation are the main foundations in creating a harmonious atmosphere. In addition, the role of religious and community leaders as communication bridges strengthens existing relationships. Religious harmony in Karangturi is created through harmonious social interactions and the community's commitment to maintaining the values ​​of togetherness.